2001
DOI: 10.1186/cc1015
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide infusion and nitric oxide inhalation in patients with acute respiratory distress syndrome

Abstract: Aim: To study the effects of infusion of atrial natriuretic peptide (ANP) versus the inhalation of nitric oxide (NO) in patients with an early acute respiratory distress syndrome (ARDS). Methods: Ten patients with severe ARDS were studied in a crossover study design, within 72 hours after starting mechanical ventilation. We studied the effects of ANP infusion (10 ng/kg/min for 1 hour) and of inhalation of NO (20 ppm for 1 hour) on hemodynamic and respiratory patient par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a cohort of 40 individuals with acute lung injury requiring mechanical ventilation with positive end-expiratory pressure (PEEP), ANP administration improved lung injury and oxygenation 95 . In contrast, Bindels et al 96 observed no difference in pulmonary gas exchange in ten patients with acute respiratory distress syndrome who received ANP. Large, randomized controlled trials are warranted to evaluate the use of exogenous ANP as a potential therapeutic agent for the treatment of infection-induced lung injury.…”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%
“…In a cohort of 40 individuals with acute lung injury requiring mechanical ventilation with positive end-expiratory pressure (PEEP), ANP administration improved lung injury and oxygenation 95 . In contrast, Bindels et al 96 observed no difference in pulmonary gas exchange in ten patients with acute respiratory distress syndrome who received ANP. Large, randomized controlled trials are warranted to evaluate the use of exogenous ANP as a potential therapeutic agent for the treatment of infection-induced lung injury.…”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%